2009
DOI: 10.1021/jp807122m
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel RRKM-TST and Direct-Dynamics VTST Study of the Reaction of Hydroxyl Radical with Furan

Abstract: The kinetics and mechanism of the reaction of OH with furan have been theoretically studied. The potential energy surface for each possible pathway has been investigated by employing DFT, G3MP2, and CCSD methods. The potential energy surface consists of one hydrogen-bonded complex and two energized intermediates. Three different pathways are suggested to be possible for the title reaction. The most probable channel is the hydroxyl radical addition to the C(2) position on the furan ring to cause the ring-openin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 33 publications
4
29
0
Order By: Relevance
“…A pre-reaction complex is found based on IRC analysis, but its influences are not accounted for in the present rate constant calculations as it is likely to be unimportant in the temperature ranges of this study . The computed rate constant is in good agreement with CCSD(full)/6-11+G(3df,2p) RRKM calculations for the reaction of ȮH radical with furan computed recently by Mousavipour et al [63]. They also concluded that ȮH radical addition to C3 of furan, or abstraction of any of the ring–H bonds, was unimportant in comparison with this addition process.…”
Section: Kinetic Model Developmentsupporting
confidence: 85%
“…A pre-reaction complex is found based on IRC analysis, but its influences are not accounted for in the present rate constant calculations as it is likely to be unimportant in the temperature ranges of this study . The computed rate constant is in good agreement with CCSD(full)/6-11+G(3df,2p) RRKM calculations for the reaction of ȮH radical with furan computed recently by Mousavipour et al [63]. They also concluded that ȮH radical addition to C3 of furan, or abstraction of any of the ring–H bonds, was unimportant in comparison with this addition process.…”
Section: Kinetic Model Developmentsupporting
confidence: 85%
“…The competition between addition and abstraction channels has also been indicated by several studies in which theoretical approaches have been used to determine the potential energy surfaces and kinetics for reactions R1-R3. [27][28][29][30][31][32] Such approaches indicate that addition of OH to the C2/C5 position of the furan ring dominates under conditions relevant to low-temperature combustion for R1, [27][28][29] R2, [29][30][31] and R3, 29 owing to resonance stabilisation. The predicted kinetics 28,29 for R1 are in good agreement with measurements at temperatures below 425 K. [21][22][23]26 However, the predicted kinetics indicate that addition channels for R1 dominate at temperatures below 2000 K, in conflict with the observations by Elwardany et al 25 which indicate that abstraction channels dominate at temperatures above 1000 K. For R2 and R3, the predicted kinetics 29,31,32 overestimate the observations made by Elwardany et al, 25 although the predicted kinetics for R2 31 do reproduce the room temperature measurements.…”
Section: Oh + F → Products (R1)mentioning
confidence: 99%
“…Theoretical studies of the reactions of OH radicals with furan, 34 2-methylfuran, 35,36 and 3-methylfuran 37 all conclude that the dominant pathway at room temperature involves OH radical addition at the 2-or 5-positions, to form RC(O)CR′ CHC…”
mentioning
confidence: 99%